Possible Interactions between the Biosynthetic Pathways of Indole Glucosinolate and Auxin - Malka, Siva K.; Cheng, Youfa (Frontiers in Plant Science, 2017)
Glucosinolates (GLS) are a group of plant secondary metabolites mainly found in Cruciferous plants that share a core structure consisting of a β-thioglucose moiety and a sulfonated oxime, but differ by a variable side chain derived from one of several amino acids. These compounds are hydrolyzed upon cell damage by thioglucosidase (myrosinase), and the resulting degradation products are toxic to many pathogens and herbivores. Human beings use these compounds as flavor compounds, anti-carcinogens, and bio-pesticides. GLS metabolism is complexly linked to auxin homeostasis. Indole GLS contributes to auxin biosynthesis via metabolic intermediates indole-3-acetaldoxime (IAOx) and indole-3-acetonitrile (IAN). IAOx is proposed to be a metabolic branch point for biosynthesis of indole GLS, IAA and camalexin. Interruption of metabolic channeling of IAOx into indole GLS leads to high-auxin production in GLS mutants. IAN is also produced as a hydrolyzed product of indole GLS and metabolized to IAA by nitrilases (NIT) enzymes. In this review, we will discuss current knowledge on involvement of GLS in auxin homeostasis.